1981
DOI: 10.2337/diacare.4.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Biosynthetic Human Insulin and Characteristics of Its Effect

Abstract: In the last 2 years we have developed a new method for determining insulin biologic activity with the help of the glucose-controlled insulin infusion system (GCIIS). Primarily this closed-loop system infuses insulin. But to prevent hypoglycemia, it can in addition, infuse glucose below a certain blood glucose minimum. This effect is used to reproduce insulin biologic activity. After subcutaneous injection of the insulin to be tested in healthy persons (not in insulin-dependent diabetic subjects), the blood glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Except for somewhat lower plasma free-insulin levels observed several hours after injection of human insulin, consistent with some reports of a shorter duration of action of subcutaneously injected human insulin (39,40), we found no difference in plasma free-insulin and glucose profiles when purified porcine or human insulin was injected. Similar results have generally been found (41,42) and are readily explained by the fact that these insulins have virtually identical intrinsic activity (41,42) and by the fact that the patients studied have had antibodies that bound porcine and human insulin indistinguishably (43) as in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Except for somewhat lower plasma free-insulin levels observed several hours after injection of human insulin, consistent with some reports of a shorter duration of action of subcutaneously injected human insulin (39,40), we found no difference in plasma free-insulin and glucose profiles when purified porcine or human insulin was injected. Similar results have generally been found (41,42) and are readily explained by the fact that these insulins have virtually identical intrinsic activity (41,42) and by the fact that the patients studied have had antibodies that bound porcine and human insulin indistinguishably (43) as in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, there may be dose-related absorption, lower doses of subcutaneous insulin masking a possible preferential absorption of the human insulin preparation. In this respect, the present study pointed more clearly to differences after injection of 9.6 U (approximately 0.15 U/kg) and the study of Botterman et al 5 …”
Section: Dose Differencessupporting
confidence: 59%
“…Previous results (Keen, Pickup, Bilous, Glynne, Viberti, Jarrett and Marsden 1980;Raptis, Karaiskos, Enzmann, Hatzidakis, Zoupas, Souvatzoglou, Diamantopoulos and Moulopoulos 1981) suggested that the biosynthetic molecule might be more active than PPI, perhaps due to a higher skin absorption rate of BHI (Bottermann et al 1981). However, the failure to correlate plasma glucose with serum insulin concentration in normal subjects (Galloway, Spradlin, Rott and Fineberg 1981) and the considerable intra-and inter-subject variations indicate that it is unlikely that such differences have a physiological meaning.…”
Section: Discussionmentioning
confidence: 92%
“…Part of those studies either on biochemical or clinical grounds have been already published Received: 5 Dec. 1983 Accepted: 28 May 1984 {Owens, Hayes, Alberti, Jones, Heding, Home and Burrin 1981;DeMeyts, Halban mdHepp 1981 ;Bottermann, Gyaram, Wahl, Ermler and Lebender 1981;Wings, Ehrhardt and Enzmann (1981). However, considerable discrepancies have arisen from the published reports.…”
Section: Introductionmentioning
confidence: 97%